Trends in Oropharyngeal Cancer Incidence Among Adult Men and Women in the United States From 2001 to 2018 - Guo, Fangjian; Chang, Mihyun; Scholl, Matthew; McKinnon, Brian; Berenson, Abbey B. (Frontiers in Oncology, 2022)
Background: The human papillomavirus (HPV) vaccine was approved in 2006 and has been shown to decrease vaccine-related HPV types in the oropharynx. Its impact on the incidence of HPV-related oropharyngeal squamous cell carcinoma (OPSCC) has not been examined. We investigated the impact of HPV vaccination on the incidence of HPV-related OPSCC in the US among male and female adults from different age groups. Methods: The US Cancer Statistics 2001–2018 database and the National Cancer Institute (NCI)’s Surveillance Epidemiology and End Results (SEER) program were used in this study. OPSCC incidence was age-adjusted to the US standard population in 2000. Cause-specific 5-year survival probability was calculated using 60 monthly intervals in SEER*Stat software. Results: Incidence of HPV-related OPSCC was much higher in males than in females. Age-adjusted annual incidence of OPSCC was significantly lower in 2014-2018 than in 2002-2006 among males 20-44 years old (11.4 vs 12.8 per 1,000,000, rate ratio 0.89, 95% confidence interval 0.84-0.93) and among females 20-44 years old (3.0 vs 3.6 per 1,000,000, rate ratio 0.86, 95% confidence interval 0.78-0.95), but increased in both 45-64 year old and 65+ year old males and females. Joinpoint regression revealed a significant joint in the HPV-OPSCC incidence trend for 20-44-year-old males in 2008 at which time the incidence began to decrease. Except for 20-44 year old females (74.8% in 2002-2006 vs. 75.7% in 2009-2013, p=0.84), cancer-specific 5-year survivals significantly improved for males and females of all age groups. Conclusions: HPV-related OPSCC was much more common in males. Incidence of HPV-related OPSCC declined among young adults during the vaccination era compared with pre-vaccination era. Cancer-specific 5-year survival was significantly improved in young males but not in young females.